Aplikasi WebAR Berbasis Marker untuk Visualisasi Tengkorak Manusia Tiga Dimensi pada Pembelajaran IPA - Wicaksono, Muhammad Azrul; Dijaya, Rohman (LPPM STT Terpadu Nurul Fikri, 2026)
Science learning requires visual media capable of explaining abstract concepts clearly, particularly in the topic of the human skeletal system. One subject that students often find difficult to understand is the structure of the human skull due to its level of complexity. This study aims to develop an Augmented Reality (AR)-based science learning medium using marker-based AR integrated into an interactive Flipbook utilizing WebAR technology. The research method employed is Research and Development (R&D) with the ADDIE development model, which encompasses the stages of analysis, design, development, implementation, and evaluation. The results indicate that the developed learning medium is capable of displaying interactive three-dimensional visualizations of the human skull through a web browser without requiring the installation of any additional applications. Functional testing and feasibility evaluation demonstrate that this learning medium is suitable for use, with a feasibility percentage of 75.94%, indicating that the medium received a positive response from users. Therefore, this WebAR-based learning medium can serve as an innovative alternative to support conceptual understanding and enhance students' learning interest in science education.